Effect of drinking saline water on performance, digestibility and nitrogen utilization of growing camels feed different quality roughages - Abdel-Wahed, A.M. (International Journal of Environment, Agriculture and Biotechnology, 2021)
This study was conducted to evaluate the effect of three roughages that were fed ad lib. with two types of water on feed intake, digestibility, water utilization and performance of growing she-camels. Twenty-four healthy growing she-camels (30-36 months old and 448.50 ± 29.30 kg body weight) were housed individually in metabolic cages and randomly allotted to three treatments. The experiment lasted for 60 days. Three roughages were Egyptian clover hay to represent optimum grazing conditions, rice straw to represent dry season grazing and Atriplex halimus to represent arid rangelands dominated by halophytes. Roughages offered to camels ad lib. The concentrates used were corn grains and cottonseed meal. Concentrate intakes calculated, per unit metabolic body weight (kg0.73). Final body weight and ADG were affected by roughages. Nutrients intake was affected (P<0.05) by roughage type but not for drinking water and their interaction. Camels fed Atriplex had higher (P<0.05) in dry matter intake, roughage intake and roughage (% DMI) than hay and straw. Corn intake was greater (P<0.05) in camels fed Atriplex and straw whereas, was lower (P<0.05) in camels fed hay. Camels fed hay had higher (P<0.05) in dry matter digestibility followed by straw and then Atriplex. Organic matter, crude fiber and Nitrogen free extract digestibility were higher (P<0.05) in camels fed hay and straw as compared to Atriplex whereas, crude protein was higher (P<0.05) in Atriplex and hay as compared to straw. Free water intake, feed water, total water intake and fecal water were higher (P<0.05) in camels fed Atriplex as compared to hay and straw. Urinary water was higher (P<0.05) in camels fed Atriplex followed by hay and then straw. Free water intake, feed water, total water intake and fecal water were higher (P<0.05) in camels fed Atriplex as compared to hay and straw. Urinary water excretion was higher (P<0.05) in camels fed Atriplex followed by hay and then straw. In conclusion, camels fed on Atriplex showed a clear improvement in growth, digestibility, and nitrogen utilization in a similar way to camels fed on hay.